Artificial leather and artificial leather manufacturing method
Patent Information
- Application Number
- JP2024158831
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-13
- Filing Date
- 2024-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0016】 本発明によれば、本革に近い質感や風合いを有し、優れた強度、柔軟性、浸水時の保形性を有する人工皮革を得ることができる。本発明によれば、生分解性が高く、製造過程ないしは使用後においても環境負荷が小さい人工皮革を得ることができる。本発明に係る人工皮革は、製造に用いた柿渋や多価アルコール、植物性のワックスを塗布することにより、撥水性や抗菌性を持続させることができる。また、本発明に係る人工皮革は、水で煮込むことにより液状、ゾル状ないしペースト状に戻すことができるので、不要になっても廃棄せずに、再び新しい人工皮革にリサイクルすることができる。
Smart Images

Figure 2025041576000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an artificial leather and a method for producing the artificial leather. [Background technology]
[0002] Leather products range from small items such as shoes, bags, pass cases, and belts to clothing and furniture such as chairs. The leather used in these products can be broadly divided into genuine leather (leather made from the skin of animals such as cows, horses, and sheep) and artificial leather (leather made to resemble genuine leather without using animal skin). In recent years, issues with genuine leather have been pointed out, such as high manufacturing costs, concerns about animal welfare, and the large environmental impact of the manufacturing process, and there has been a movement to shift to the use of artificial leather.
[0003] On the other hand, conventional artificial leathers also use resins such as polyurethane and vinyl chloride, which are made from petroleum, and therefore have a problem in terms of reducing the consumption of limited petroleum resources. In addition, the resins are poorly biodegradable, and they also have a large environmental impact in that they promote global warming by emitting large amounts of carbon dioxide during the production of resin from petroleum and the incineration of the resin products (including combustion by thermal recycling, etc.). For these reasons, there is a demand for the development of artificial leathers with a smaller environmental impact. For example, Patent Document 1 discloses a fibrous substrate made of an elastic resin containing ultrafine fibers and plant-derived components, which has the feel of natural nubuck leather and the nap of natural suede leather, while being flexible and highly abrasion-resistant. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-044292 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, although the sheet-like material described in Patent Document 1 can also contain a resin made from a plant-derived component, it has not yet achieved the non-use of petroleum resources. In other words, even in light of the prior art, it cannot be said that artificial leather with low environmental impact is in sufficient supply. The present invention has been made to solve the above problem, and has an object to provide artificial leather that is highly biodegradable and has low environmental impact during the manufacturing process or after use. [Means for solving the problem]
[0006] As a result of intensive research, the present inventors have found that by mixing and heating "persimmon tannin, gelling agent, polyhydric alcohol and cellulose fiber", "persimmon tannin, gelling agent and animal and plant waste" or "gelling agent, cellulose fiber and animal and plant waste", and then molding and solidifying it, it is possible to produce artificial leather that has a texture similar to that of genuine leather and has excellent strength, flexibility and shape retention when immersed in water. Based on this knowledge, the present inventors have completed the following inventions.
[0007] (1) A first embodiment of the artificial leather according to the present invention contains persimmon tannin, a gelling agent, a polyhydric alcohol, and cellulose fibers.
[0008] (2) A second embodiment of the artificial leather according to the present invention comprises persimmon tannin, a gelling agent, and animal and plant waste.
[0009] (3) A third embodiment of the artificial leather according to the present invention comprises a gelling agent, cellulose fibers, and animal and plant waste.
[0010] (4) In the artificial leather according to the first aspect, the solid content of each substance may be as follows: Persimmon tannin: 0.1% by mass or more to 30% by mass or less, Gelling agent: more than 2% by mass to 45% by mass or less, Polyhydric alcohol: more than 0% by mass to 90% by mass or less, Cellulose fiber: more than 0% by mass to 30% by mass.
[0011] (5) In the artificial leather according to the second aspect, the solid content of each substance may be as follows: Persimmon tannin: 0.1% by mass or more to 30% by mass or less, Gelling agent: more than 2% by mass to 45% by mass or less, Animal and plant waste: More than 0% by mass to 97% by mass or less.
[0012] (6) In the artificial leather according to the third aspect, the solid content of each substance may be as follows: Gelling agent: more than 2% by mass to 45% by mass or less, Cellulose fiber: more than 0% by mass to 30% by mass or less, Animal and plant waste: More than 0% by mass to 97% by mass or less.
[0013] (7) A method for producing an artificial leather according to the present invention (sometimes simply referred to as "the present production method") includes a dissolving step of heating a mixture selected from the group consisting of the following (A) to (C) to a temperature at which a gelling agent dissolves to obtain a dissolved product, a shaping step of forming the dissolved product into a predetermined shape and then solidifying it by dissipating heat to obtain a solidified product, and a drying step of drying the solidified product: (A) A mixture containing persimmon tannin, a gelling agent, a polyhydric alcohol, cellulose fiber, and water. (B) A mixture containing persimmon tannin, a gelling agent, animal and plant waste, and water. (C) A mixture comprising a gelling agent, cellulose fibers, animal and plant waste, and water.
[0014] (8) The artificial leather according to the second embodiment may further contain animal and plant waste.
[0015] (9) In the present invention, the cellulose fiber may be bacterial cellulose. Effect of the Invention
[0016] According to the present invention, it is possible to obtain an artificial leather having a texture and feel similar to that of genuine leather, and excellent strength, flexibility, and shape retention when immersed in water. According to the present invention, it is possible to obtain an artificial leather that is highly biodegradable and has a small environmental impact during the manufacturing process or after use. The artificial leather according to the present invention can maintain its water repellency and antibacterial properties by applying persimmon tannin, polyhydric alcohol, or vegetable wax used in the manufacturing process. Furthermore, the artificial leather according to the present invention can be returned to a liquid, sol, or paste state by boiling it in water, so that it can be recycled into new artificial leather again without being discarded even when it is no longer needed. [Brief description of the drawings]
[0017] [Figure 1] 1 is a photograph of the artificial leather (invention product) containing persimmon skin of Example 1. [Diagram 2] 1 is a photograph of the artificial leather containing carrot pomace of Example 2. [Diagram 3] 1 is a photograph of a small handbag made using the artificial leather of Example 1. [Figure 4] 1 is a photograph of a business card holder made using the artificial leather of Example 2. [Diagram 5] Photographs of artificial leather colored with red iron oxide of various colors. [Figure 6] Photographs of artificial leather colored with edible plant powders (butterfly pea extract powder, matcha powder, and pumpkin powder). [Figure 7] This is a table showing the evaluation results (thickness, appearance, bending resistance, tensile strength, tear load, and shape retention when hydrophilic) of artificial leather containing different combinations of various materials (persimmon tannin, kappa-type carrageenan, sorbitol, BC dispersion, and carrot pomace). [Figure 8] 1 is a table showing the evaluation results of artificial leather containing various materials (persimmon tannin, kappa-type carrageenan, BC dispersion, and persimmon peel) in different combinations. [Figure 9] 1 is a table showing the evaluation results of artificial leathers containing different amounts of persimmon tannin. [Figure 10]1 is a table showing the evaluation results of artificial leather containing different amounts of kappa-type carrageenan. [Figure 11] 1 is a table showing the evaluation results of artificial leathers containing different amounts of sorbitol. [Figure 12] 1 is a table showing the evaluation results of artificial leathers containing different amounts of cellulose fibers. [Figure 13] 1 is a table showing the evaluation results of artificial leathers containing various gelling agents. [Figure 14] 1 is a table showing the evaluation results of artificial leather containing various types of vegetable waste. [Figure 15] 1 is a table showing the evaluation results of artificial leather containing different proportions of vegetable waste (carrot pomace or persimmon peel). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] The present invention will be described in detail below. The present invention provides an artificial leather and a manufacturing method thereof. The artificial leather according to the present invention can be obtained by the manufacturing method.
[0019] <Dissolution process> The dissolving step is a step of obtaining a dissolved material by heating a mixture containing the material of the artificial leather to a temperature at which the gelling agent dissolves. Here, the mixture is one of the following (A) to (C); (A) First embodiment: A mixture containing persimmon tannin, a gelling agent, a polyhydric alcohol, cellulose fibers and water. (B) Second embodiment: A mixture containing persimmon tannin, a gelling agent, animal and plant waste, and water. (C) Third embodiment: A mixture comprising a gelling agent, cellulose fibers, animal and plant waste and water.
[0020] Persimmon juice is a liquid obtained by squeezing the juice from unripe persimmons harvested while still green, and fermenting and maturing the juice, and generally has a reddish-brown, semi-transparent appearance. Persimmon juice is a component that enhances the water resistance, tear strength, durability, and water repellency of the artificial leather according to the present invention, and imparts antibacterial properties. Commercially available persimmon juice can be used.
[0021] The content of persimmon tannin can be appropriately set depending on the use of the leather, the desired texture, the content of other ingredients, etc. The content of persimmon tannin in the artificial leather can be, for example, lower limit, in terms of solid content, more than 0 mass%, 0.01 mass% or more, 0.02 mass% or more, 0.03 mass% or more, 0.04 mass% or more, 0.05 mass% or more, 0.06 mass% or more, 0.07 mass% or more, 0.08 mass% or more, 0.09 mass% or more, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, 0.5 mass% or more, 0.6 mass% or more, 0.7 mass% or more, 0.8 mass% or more, 0.9 mass% or more, 0.1 mass% or more, 0.2 mass% or more, 0.3 mass% or more, 0.4 mass% or more, 0.5 ...6 mass% or more, 0.7 mass% or more, 0.8 mass% or more, 0.9 mass% or more, 0.8 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0.9 mass% or more, 0. Examples of the upper limit include 40 mass% or less, 39 mass% or less, 38 mass% or less, 37 mass% or less, 36 mass% or less, 35 mass% or less, 34 mass% or less, 33 mass% or less, 32 mass% or less, 31 mass% or less, 30 mass% or less, 29 mass% or less, etc., in terms of solid content.
[0022] A gelling agent refers to a substance that gels and solidifies a liquid, and may also be called a thickening agent, a thickening stabilizer, or a glue. A gelling agent is a component that imparts bending resistance and flexibility to the artificial leather according to the present invention, and by adding the gelling agent, it is possible to prevent cracks and chips from occurring when the leather is folded. Examples of the component include polymers such as proteins and polysaccharides, and surfactants. More specific examples of proteins include collagen and gelatin. More specific examples of polysaccharides include carrageenan, locust bean gum, gellan gum, xanthan gum, agar, kudzu starch, starch, pectin, glucomannan, tamarind seed gum (tamarind gum), and curdlan. Commercially available gelling agents can be used.
[0023] The content of the gelling agent can be appropriately set depending on the use of the leather, the desired texture, the content of other components, etc. The content of the gelling agent in the artificial leather can be, for example, at least 2% by mass, 2.1% by mass or more, 2.2% by mass or more, 2.3% by mass or more, 2.4% by mass or more, 2.5% by mass or more, 2.6% by mass or more, 2.7% by mass or more, 2.8% by mass or more, 2.9% by mass or more, 3.0% by mass or more, 3.1% by mass or more, 3.2% by mass or more, 3.3% by mass or more, 3.4% by mass or more, 3.5% by mass or more, 3.6% by mass or more, 3.7% by mass or more, 3.8% by mass or more, 3.9% by mass or more, based on the solid content. Examples of the upper limit include 4 mass% or more, 4.1 mass% or more, 4.2 mass% or more, 4.3 mass% or more, 4.4 mass% or more, 4.5 mass% or more, 4.6 mass% or more, 4.7 mass% or more, 4.8 mass% or more, 4.9 mass% or more, 5 mass% or more, and the upper limit, in terms of solid content, can be 50 mass% or less, 49 mass% or less, 48 mass% or less, 47 mass% or less, 46 mass% or less, 45 mass% or less, 44 mass% or less, 43 mass% or less, 42 mass% or less, 41 mass% or less, 40 mass% or less, and the like.
[0024] A polyhydric alcohol is an organic compound having two or more alcoholic hydroxyl groups in one molecule, and is also called a polyol. The polyhydric alcohol is a component that imparts flexibility to the artificial leather according to the present invention, and by adding the polyhydric alcohol, even if moisture is removed after the drying process, the leather does not crack or break, and can maintain its flexibility and smoothness. Specific examples of polyhydric alcohols include glycerin, sorbitol, maltitol, 1,3-butylene glycol, 1,2-pentanediol, and propylene glycol. Commercially available polyhydric alcohols can be used.
[0025] The content of the polyhydric alcohol can be appropriately set depending on the use of the leather, the desired texture, the content of other ingredients, etc. Examples of the content of polyhydric alcohol in the artificial leather include a lower limit of more than 0% by mass, 0.01% by mass or more, 0.02% by mass or more, 0.03% by mass or more, 0.04% by mass or more, 0.05% by mass or more, 0.06% by mass or more, 0.07% by mass or more, 0.08% by mass or more, 0.09% by mass or more, 0.1% by mass or more, 0.2% by mass or more, 0.3% by mass or more, 0.4% by mass or more, 0.5% by mass or more, 0.6% by mass or more, 0.7% by mass or more, 0.8% by mass or more, 0.9% by mass or more, and 1% by mass or more, and an upper limit of 95% by mass or less, 94% by mass or less, 93% by mass or less, 92% by mass or less, 91% by mass or less, 90% by mass or less, 89% by mass or less, 88% by mass or less, 87% by mass or less, 86% by mass or less, and 85% by mass or less, in terms of solid content.
[0026] In the present invention, cellulose fiber refers to fibrous cellulose or cellulose derivatives. Here, cellulose is a homopolysaccharide in which D-glucopyranose is linked by β(1→4) glycosidic bonds. Cellulose derivatives are a general term for compounds in which different substituents are introduced into the hydroxyl groups of cellulose molecules, and include cellulose ethers formed by ether bonds and cellulose esters formed by ester bonds. Examples of cellulose ethers include methyl cellulose, ethyl cellulose, ethyl methyl cellulose, carboxymethyl cellulose (CMC), carboxyethyl cellulose, hydroxyethyl cellulose, hydroxypropyl cellulose, benzyl cellulose, trityl cellulose, cyanoethyl cellulose, and aminoethyl cellulose. Examples of cellulose esters include acetyl cellulose, diacetyl cellulose, and triacetyl cellulose.
[0027] The cellulose fiber is a component that increases the strength of the artificial leather according to the present invention, such as the tensile strength. The cellulose fiber may be any fibrous cellulose or cellulose derivative, regardless of its origin, manufacturing method, the presence or absence of crystalline parts, etc., and is a concept that includes cellulose microfibrils (bundles of 10 to tens of cellulose molecules), cellulose nanofibers, cellulose derivative nanofibers such as CMC nanofibers, cellulose nanocrystals, bacterial cellulose, and bacterial nanocellulose.
[0028] The width and length of the cellulose fibers can be set appropriately; for example, the width can be 3 nm or more, 10 nm or more, 20 nm or more, 50 nm or more, several thousand nm or less, 1000 nm or less, 100 nm or less, 60 nm or less, and the length can be 100 nm or more, 1000 nm or more, 1500 nm or more, 5000 μm or less, 1000 μm or less, 500 μm or less, 100 μm or less, and the like.
[0029] The cellulose fibers may be derived from plants (pulp-derived cellulose) or may be produced by microorganisms such as acetic acid bacteria (bacterial cellulose). Among these, examples of plants from which pulp-derived cellulose is derived include wood, hemp, banana, bagasse, pineapple, and the like. On the other hand, bacterial cellulose is preferable in that, unlike pulp-derived cellulose, it is not bound to impurities such as hemicellulose and lignin, and is easy to purify, and undamaged high-quality cellulose fibers can be obtained.
[0030] The cellulose fibers may be commercially available. Examples of such commercially available products include nanofibrillated bacterial cellulose "Fibnano (registered trademark) CM-NFBC", "Fibnano (registered trademark) HE-NFBC", and "Fibnano (registered trademark) HP-NFBC" (all of which are Kusano Sakuko Co., Ltd.), "BiNFi-s Cellulose Nanofiber" (Sugino Machine Co., Ltd.), and "BiNFi-s CMC Nanofiber" (Sugino Machine Co., Ltd.).
[0031] Cellulose fibers can also be produced according to conventional methods. For example, in the case of bacterial cellulose, a microorganism capable of producing bacterial cellulose (sometimes referred to as a "BC-producing bacterium") may be cultured and purified as necessary. The microorganism may be one known as a BC-producing bacterium, and specific examples thereof include Gluconacetobacter xylinus ATCC53582 strain, Gluconacetobacter hansenii ATCC23769 strain, Gluconacetobacter xylinus ATCC700178 (BPR2001) strain, Gluconacetobacter swingsii BPR3001E strain, Acetobacter xylinum JCM10150 strain, Enterobacter sp. CJF-002 strain, and Gluconacetobacter intermedius SIID9587 strain (accession number NITE BP-01495).
[0032] The BC-producing bacteria can be cultured under known culture conditions for the species, such as an aeration rate of 1-10 L / min, a rotation speed of 100-800 rpm, a temperature of 20-40°C, and a culture period of 1-7 days. The medium may be a known medium used for culturing the species, such as Hestrin-Schramm standard medium (HS medium). A dispersant (hydroxypropyl cellulose, carboxymethyl cellulose, hydroxyethyl cellulose, etc.) may be added to the medium.
[0033] Since the culture solution contains bacterial cellulose, it may be used as it is as "cellulose fiber" or may be purified as necessary. For example, purification may be performed by adding an aqueous solution of sodium hydroxide (NaOH) to the culture solution to dissolve the bacterial cells, centrifuging the solution, and removing the supernatant containing the bacterial cell lysate. An example of such a method is to add water to the precipitate, stir the solution, and then centrifuging the solution to remove the supernatant, repeating this process until the pH of the precipitate becomes 7 or less. This makes it possible to obtain a liquid in which bacterial cellulose is dispersed in water (bacterial cellulose dispersion), which can be used as "cellulose fiber".
[0034] The cellulose fiber is a component that gives strength to the artificial leather according to the present invention. The content ratio of the cellulose fiber can be appropriately set according to the use of the leather, the desired texture, the content ratio of other components, and the like. In the mixture, the specific content ratio of the cellulose fiber can be exemplified by, for example, the lower limit being 0.01 parts by mass or more, 0.05 parts by mass or more, 0.1 parts by mass to 0.2 parts by mass or more, 0.3 parts by mass or more, and the upper limit being 10 parts by mass or less, 9 parts by mass or less, 8 parts by mass or less. In addition, in the artificial leather, the specific content ratio of the cellulose fiber can be exemplified by, for example, the lower limit being 0.01 parts by mass or more, 0.05 parts by mass or more, 0.1 parts by mass to 0.2 parts by mass or more, 0.3 parts by mass or more, and the upper limit being 10 parts by mass or less, 9 parts by mass or less, 8 parts by mass or less.
[0035] Animal and plant waste refers to animal waste and / or plant waste. Specific examples of plant waste include vegetable waste, skins and seeds of fruits such as persimmons, citrus fruits, bananas, apples, grapes, and peaches, grain husks, persimmon tannin pomace, tea leaves after extraction, coffee grounds, food residues, plant branches and leaves, fruits, roots, wood chips, rice straw, rice husks, thinning materials, and combinations thereof. Specific examples of animal waste include inedible parts such as bones and skins of livestock and seafood, shells, eggs, feathers, food residues, etc.
[0036] The animal and plant waste is a component that gives the artificial leather the texture and strength of real leather. The thickness of the artificial leather can be adjusted by the content, type, and processing mode of the animal and plant waste, such as crushing. Therefore, the content ratio of the animal and plant waste can be appropriately set depending on the use of the leather, the desired texture, the content ratio of other components, etc. Examples of the content of animal and plant waste in the artificial leather include a lower limit of more than 0% by mass, 0.1% by mass or more, 1% by mass or more, 2% by mass or more, 3% by mass or more, 4% by mass or more, 5% by mass or more, 6% by mass or more, 7% by mass or more, 8% by mass or more, 9% by mass or more, 10% by mass or more, 15% by mass or more, 20% by mass or more, 25% by mass or more, 30% by mass or more, 35% by mass or more, 40% by mass or more, 45% by mass or more, 50% by mass or more, and 55% by mass or more, and an upper limit of 99% by mass or less, 98% by mass or less, 97% by mass or less, 96% by mass or less, 95% by mass or less, 93% by mass or less, 91% by mass or less, 90% by mass or less, 88% by mass or less, 86% by mass or less, 84% by mass or less, 82% by mass or less, 80% by mass or less, and 78% by mass or less, in terms of solid content.
[0037] Water is an ingredient for homogeneously mixing the other raw materials. Therefore, water should be added in an amount sufficient to homogeneously mix the other raw materials. In other words, the amount of water added or the content ratio of water in the mixture can be appropriately set depending on the types and amounts of other materials, the amount of water originally contained in the other materials, room temperature, humidity, operability in the manufacturing process, etc.
[0038] The artificial leather according to the present invention may further contain desired components such as colorants (organic pigments, inorganic pigments, colorants derived from plants or animals such as turmeric, indigo, and sea slugs, etc.). When such desired components are to be contained, they may be added to the mixture in the dissolving step.
[0039] The dissolving step is a step of dissolving the gelling agent contained in the mixture to make the entire mixture liquid, sol or paste. Therefore, the heating temperature in this step can be appropriately set according to the type of gelling agent within a range in which the gelling agent dissolves and does not lose its function of solidifying again when heat is released. For example, when gelatin is used as the gelling agent, the heating temperature can be about 50 to 65°C, when agar is used, 90°C or higher, when carrageenan is used, about 70 to 90°C, and when locust bean gum is used, 85°C or higher, etc. can be exemplified.
[0040] <Forming process> The molding process is a process in which the melt obtained in the melting process is molded into a predetermined shape, and then solidified by dissipating heat. Since the melt is in a liquid, sol or paste form, it can be molded into a desired shape and thickness by pouring an appropriate amount of it into a mold of a desired shape. The shape can be appropriately set according to the final product, or according to versatility and ease of handling such as transportation. For example, it can be a three-dimensional shape such as a hollow sphere, hemisphere, or cylinder, in addition to a rectangular or strip shape.
[0041] Warming the mold beforehand prevents the gelling agent from cooling and solidifying rapidly, and allows the melt to be poured evenly into the mold. In addition, after drying, shrinkage occurs as the water evaporates, so it is preferable to select the size of the mold in anticipation of shrinkage to about 1 / 2 to 2 / 3 in size and 1 / 5 to 2 / 3 in thickness. In addition, before or after solidification, the surface can be scraped to give a pattern, embossed, engraved, etc., or holes required for product processing such as belt holes can be made.
[0042] The temperature at which the molded melt is cooled and solidified can be set appropriately based on the solidification temperature of the gelling agent, depending on the type and amount of the gelling agent and other materials used, etc. For example, when gelatin is used as the gelling agent, it can be left in a relatively low-temperature environment such as a refrigerator, and when agar, carrageenan, or locust bean gum is used, it can be solidified by leaving it in a room temperature environment.
[0043] <Drying process> The drying process is a process for drying the solidified product obtained in the molding process. The drying conditions can be appropriately set depending on the type and amount of materials used, the desired texture, the production amount, etc., but can be carried out, for example, by leaving the product at room temperature for several days in a well-ventilated space. After drying, shrinkage occurs as the moisture evaporates, so placing weights on both ends or drying while pressing with a breathable material such as a net can prevent the leather from curving.
[0044] The artificial leather according to the present invention can be used for the manufacture of ordinary leather products. Examples of such leather products include bags, shoes, belts, wallets, pass cases, business card holders, key cases, pen cases, smartphone cases, glasses cases, book covers, backpacks, clothing, hats, gloves, accessories, and strings. In addition, since it has water repellency, it can be used as a substitute for plastics in outdoor products such as tents, leisure sheets, and leisure chairs, gardening products, and rain gear such as umbrellas, raincoats, and rain boots. In addition, since persimmon tannin has antibacterial properties, it can be used for sofas and chairs in public facilities such as hospitals, tablecloths, placemats, curtains, carpets, and sanitary products such as sanitary masks. It can also be used for building materials such as wall materials, ceiling materials, and floor materials, and interior products such as lighting.
[0045] The present invention will be described below with reference to examples. Note that the technical scope of the present invention is not limited to the characteristics shown in these examples. EXAMPLES
[0046] <Test materials> (1) Preparation of cellulose fibers A dispersant (carboxymethylcellulose: CMC) was added to the HS medium (composition: bacto peptone 0.5% (w / v), yeast extract 0.5% (w / v), Na2HPO4 0.27% (w / v), citric acid 0.115% (w / v), glucose 2% (w / v)) to a final concentration of 2% (w / v). Gluconacetobacter intermedius SIID9587 strain (accession number NITE BP-01495; deposited at the National Institute of Technology and Evaluation, Patent Microorganisms Deposit Center (2-5-8 Kazusa Kamatari, Kisarazu City, Chiba Prefecture, Japan, Room 122) on December 21, 2012, which is a bacterial cellulose producer, was inoculated and the aeration volume was adjusted to 100 s. Bacterial cellulose was produced by aeration and agitation culture for 3 days under conditions of 7-10 L / min, 200-500 rpm, and 30°C. Then, an equal volume of 4% (w / v) NaOH aqueous solution was added to the culture solution, and the cells were dissolved by rotating at 70°C and 150 rpm for 2 hours. The solution was neutralized by adding 6N H2SO4, centrifuged, and the supernatant was removed to recover the precipitate, thereby removing the water-soluble bacterial components. Ultrapure water was added thereto, centrifuged, and the supernatant was removed. This procedure was repeated until the pH of the precipitate reached about 7 in a wet state, and a liquid in which bacterial cellulose was dispersed (BC dispersion) was obtained.
[0047] A part of the BC dispersion was taken, dried, and the bone dry weight was measured, and the concentration of cellulose (bacterial cellulose or bacterial cellulose bound to a dispersant) was calculated based on the measurement result. The cellulose concentration in the BC dispersion was adjusted to 1 mass% by adding water.
[0048] The cellulose fibers contained in the BC dispersion were observed using a transmission electron microscope, and were found to be nanofibers with a fiber width of 20 to 60 nm and a fiber length of 100 to 500 μm. For the observation, 10 μL of the BC dispersion, which had been adjusted to a cellulose concentration of approximately 0.001% (w / w), was dropped onto a formvar-coated copper grid and air-dried, after which 5 μL of a 5% (w / v) gadolinium acetate aqueous solution was dropped onto it, and after 10 seconds, the excess liquid was removed with filter paper to obtain a negative stained specimen. This was observed using a transmission electron microscope at an accelerating voltage of 80 kV and a magnification of 30,000 times, and the width and length of the cellulose fibers were measured based on the observed images.
[0049] (2) Other materials The commercially available products shown in Table 1 were used. The plant waste used was banana, apple or white peach peel (unheated), astringent persimmon peel (unheated, frozen storage), and carrot pomace (unheated, residue obtained by squeezing grated carrot to remove moisture). [Table 1]
[0050] <Evaluation method> The thickness of the prepared artificial leather was measured, and its appearance was photographed. In addition, bending resistance, tensile strength, tear load, and shape retention when hydrophilic were evaluated by the methods described in (1) to (4) below. Evaluation items that could not be measured because test pieces could not be prepared due to reasons such as easy tearing are indicated with "ND".
[0051] (1) Bending resistance The prepared artificial leather was folded in half and then returned to its original state, and visually inspected for the presence or absence of cracks, creases, etc.
[0052] (2) Tensile strength From the artificial leather thus produced, a type A22 dumbbell-shaped tensile test piece was produced in accordance with JIS K7139 "Plastics - Test Pieces." That is, the test piece had the shape and dimensions shown below. [Test piece shape 1] TIFF2025041576000003.tif41165
[0053] Next, the tensile strength was measured according to JIS K7161-1 "Plastics - Determination of tensile properties". That is, the test piece was attached to the jig (up to 50N) of a tensile testing machine (tabletop precision universal testing machine AGS-X, Shimadzu Corporation) and pulled at a pulling speed of 5mm / min until it broke. The maximum load at this time was measured and the tensile strength was calculated using the following formula 1. The tensile strength was calculated as the average value of three specimens for each sample. Formula 1: Tensile strength (MPa) = Maximum load at break (N) / Cross-sectional area of test piece (thickness x width) (mm 2 )
[0054] Regarding tensile strength, according to Reference 1 (※), the tensile strength of commercially available genuine leather and various artificial leathers (measured according to ISO3376) is 0.2 to 39.5 N / mm 2 It has been reported that the range of tensile strength was within the range of 0.2 MPa (Table 2). Based on this, in this example, a tensile strength of 0.2 MPa or more was evaluated as being suitable for use as a product (having tensile strength). *Reference 1: Michael Meyer et al., Comparison of the Technical Performance of Leather, Artificial Leather, and Trendy Alternatives, Coatings 2021, 11, 226. https: / / doi.org / 10.3390 / coatings11020226
[0055] (3) Tearing load Test pieces were prepared from the artificial leather and the tear load was measured according to JIS K6557-3 "Leather test methods - Physical tests - Part 3: Measurement of tear load by single edge method." That is, the test pieces were of "standard" size, as shown below, with a 50 mm long cut made with a sharp blade from the end on the long axis to the center line. [Test piece shape 2] TIFF2025041576000004.tif41165
[0056] Next, the test piece was attached to the grip of a tensile testing machine (tabletop precision universal testing machine AGS-X, Shimadzu Corporation) using the fixing method described below, and pulled at a constant speed (100±20 mm / min) until the test piece broke, and the load-elongation curve was recorded. The section from the first peak to the last peak of the load-elongation curve was equally divided into four sections, and the average value (N / mm) of the two central sections was calculated and used as the tear load (N / mm). The tear load was calculated as the average of three specimens for each sample. [Test specimen fixing method] TIFF2025041576000005.tif66165
[0057] Regarding the tear load, Reference 1 reports that the tear strength (measured according to ISO3377-1) of commercially available genuine leather and various artificial leathers is in the range of 0.5 to 82.9 N / mm (Table 2). Based on this, in this example, a tear load of 0.5 N / mm or more was evaluated as being suitable for use as a product (having tear strength).
[0058] (4) Shape retention when immersed in water The prepared artificial leather was immersed in water at room temperature for 24 hours, after which it was taken out and visually observed for changes in shape, etc.
[0059] <Example 1> Comparative evaluation of artificial leather containing cellulose fibers Comparative and inventive artificial leathers were prepared according to the formulations shown in Table 2 and evaluated. [Table 2]
[0060] (1) Preparation of comparison samples <Mixing process> All ingredients were weighed out into a pot and mixed using a spatula until homogenous. <Dissolving process> The pot containing the mixture was heated over low heat to 70-80°C, and the carrageenan was dissolved until it became a thick liquid, and the heat was turned off just before it boiled. <Molding process> The melt was poured evenly into a heat-resistant stainless steel tray (20 cm x 20 cm) that had been pre-warmed with hot water to a height of 4 mm, and left to stand at room temperature for 24 hours to solidify into a solidified product. <Drying step> The solidified material was removed from the tray, weights were placed on both ends, and the material was left to dry at room temperature for 3 days in a well-ventilated room.
[0061] (2) Creation of inventions <Mixing process> Powdered materials (sorbitol, gelling agent) were mixed in advance to form a mixed powder. Astringent persimmon peel and a small amount of water were placed in a mixer and mixed. Next, liquid or slurry-like materials (persimmon tannin, glycerin, cellulose fiber) were placed in the mixer and further mixed. Finally, the mixed powder was placed in the mixer and further mixed to form a mixture. <Dissolving process> The mixture was transferred to a frying pan and heated over low heat to 60-70°C while adding the remaining water. The mixture was heated and mixed until the gelling agent was dissolved and the mixture was smooth, resulting in a dissolved mixture. <Molding process> The melt was poured evenly into a pre-warmed heat-resistant stainless steel tray (20 cm x 20 cm) to a height of 4 mm, and left to solidify at room temperature for 2 to 3 days to produce a solidified product. <Drying process> The solidified material was removed from the tray, weights were placed on both ends, and the material was left to dry at room temperature for 3 to 5 days in a well-ventilated room.
[0062] (3) Comparative evaluation A photograph of the inventive product is shown in Figure 1. In both the comparative product and the inventive product, the solidified material shrunk by about 20-30% upon drying, becoming artificial leather with a size of about 16 cm x 16 cm, a thickness of about 3 mm, and a weight of about 25-30 g. Both the comparative product and the inventive product had a texture similar to leather derived from animal hides, and also had the Japanese-style texture of persimmon tannin. On the other hand, the comparative product had relatively low strength, and could tear when pulled with a large force. In contrast, the inventive product had high strength and did not tear even when pulled with a large force. From these results, it became clear that by adding cellulose fibers, high strength can be imparted to artificial leather using persimmon tannin.
[0063] Example 2: Examination of plant waste An artificial leather was produced by replacing "persimmon peel" with "carrot pomace" and following the composition of the invention in Table 1 and the production procedure described in Example 1 (2). A photograph of the produced artificial leather is shown in FIG. 2. As shown in FIG. 2, an artificial leather measuring approximately 16 cm x 16 cm, approximately 3 mm thick, and weighing approximately 25 to 30 g was obtained. This artificial leather had a texture similar to that of leather derived from animal skin, and also had a slightly reddish feel. In addition, this artificial leather did not tear even when pulled with a large force, and had high strength. From this result, it was revealed that even when carrot pomace is used as vegetable waste, artificial leather with high strength and excellent texture and feel can be produced, similar to the case of using persimmon peel.
[0064] <Example 3> Manufacturing leather products Using the inventive artificial leather of Example 1, a small handbag was produced according to a standard method. The result is shown in Figure 3. Also, using the artificial leather of Example 2, a business card holder was produced according to a standard method. The result is shown in Figure 4. As shown in Figures 3 and 4, all of the artificial leathers have high strength and can withstand sewing, so leather products could be produced in the same way as genuine leather.
[0065] Example 4: Cellulose fiber The "BC dispersion" (1% by mass, liquid) was replaced with commercially available cellulose fiber "BinFi-s Ima-10002" (2% by mass, slurry, raw material: plant-derived cellulose) or commercially available carboxyl methyl cellulose fiber "BinFi-s TFo-10002" (2% by mass, slurry), and an artificial leather was produced according to the composition of the invention in Table 1 and the production procedure described in Example 1 (2). As a result, an artificial leather with a size of about 16 cm x 16 cm, a thickness of about 3 mm, and a weight of about 25 to 30 g was obtained. This artificial leather had a texture similar to that of leather derived from animal skin, and also had the Japanese-style texture of persimmon tannin. In addition, it did not tear even when pulled with a large force, and had high strength. From this result, it became clear that by adding ultrafine fibers of cellulose or carboxyl methyl cellulose (cellulose derivative), high strength can be imparted to artificial leather using persimmon tannin.
[0066] <Example 5> Examination of gelling agents Artificial leather was produced by replacing "kappa carrageenan" with "iota carrageenan" or "glucomannan" and using the comparative product formulations in Table 1 and the production procedure described in Example 1 (1). As a result, an artificial leather measuring approximately 16 cm x 16 cm, approximately 3 mm thick, and weighing approximately 25 to 30 g was obtained. This artificial leather had a texture similar to that of leather derived from animal skin, and also had the Japanese-style texture of persimmon tannin. From these results, it was revealed that artificial leather with excellent texture and feel can be produced even when iota carrageenan or glucomannan is used as a gelling agent, similar to the case of using kappa carrageenan.
[0067] <Example 6> Examination of the presence or absence of persimmon tannin An artificial leather (thickness 2.56 mm) was prepared according to the composition of the invention in Table 1 and the preparation procedure described in Example 1(2), and designated as specimen A. In addition, an artificial leather (thickness 1.41 mm) was prepared according to the composition of the invention in Table 1, but omitting the persimmon tannin, and the preparation procedure described in Example 1(2), and designated as specimen B. The tensile strength (Mpa) of specimens A and B was measured according to the test method JIS K6557-2 "Measurement of tensile strength and elongation (tensile strength)". In addition, the static water resistance was measured according to the test method JIS K6550 "Leather test method (static water resistance)". The results are shown in Table 3. [Table 3]
[0068] As shown in Table 3, the tensile strength of sample A was significantly greater than that of sample B, with sample A having a tensile strength 1.5 times that of sample B. The static water resistance of sample A was also significantly longer than that of sample B. These results demonstrate that the inclusion of persimmon tannin can impart high strength and water resistance to artificial leather.
[0069] <Example 7> Examination of the possibility of coloring (1) Coloring with red iron oxide Artificial leathers were prepared according to the composition of the invention in Table 1 and the preparation procedure described in Example 1 (2), and named samples 1 to 5. However, samples 1, 2, 3, and 5 were prepared by adding 0.1 to 2 g / 100 g of black, yellow, green, and white red iron oxide (powder: 100%) in the mixing step. The results are shown in Figure 5. As shown in Figure 5, sample 4 had a reddish-brown color of persimmon tannin, and samples 1, 2, 3, and 5 had black, yellow, green, and white colors, respectively. In addition, samples 1 to 5 all had a texture and feel similar to leather derived from animal skin, and had high strength. From these results, it became clear that the color of artificial leather could be made as desired by adding red iron oxide of each color.
[0070] (2) Coloring with edible plant powder Artificial leathers were prepared according to the composition of the invention in Table 1 and the preparation procedure described in Example 1(2), and named samples 1 to 4. However, samples 1 to 3 were prepared by adding butterfly pea extract powder, matcha powder, and pumpkin powder (all of which are commercially available as edible powders) at 0.1 to 2 g per 100 g of the mixture in the mixing process. The results are shown in Figure 6. As shown in Figure 6, samples 1 to 3 had blue, green, and orange colors, respectively. In addition, samples 1 to 3 all had a texture and feel similar to leather derived from animal skin, and had high strength. From these results, it became clear that the color of artificial leather could be made as desired by adding edible plant powders of each color.
[0071] <Example 8> Study of essential components 1 The artificial leathers of Samples 1 to 11 were produced according to the formulation shown in the upper part of Fig. 7 and the production procedure described in Example 1 (2). That is, as the raw materials for the leather, Sample 1 was mixed with only carrot pomace (plant waste), Sample 2 was mixed with sorbitol (polyhydric alcohol) and carrot pomace, Sample 3 was mixed with BC dispersion (cellulose fiber) and carrot pomace, Sample 4 was mixed with kappa carrageenan (gelling agent) and carrot pomace, Sample 5 was mixed with persimmon tannin and carrot pomace, Sample 6 was mixed with persimmon tannin, BC dispersion and carrot pomace, Sample 7 was mixed with kappa carrageenan, BC dispersion and carrot pomace, Sample 8 was mixed with persimmon tannin, kappa carrageenan and carrot pomace, Sample 9 was mixed with persimmon tannin, kappa carrageenan, sorbitol and carrot pomace, and Samples 10 to 11 were mixed with persimmon tannin, kappa carrageenan, sorbitol and BC dispersion. The artificial leather thus produced was subjected to thickness measurement, external photographs, and evaluations of bending resistance, tensile strength, tear load, and shape retention when hydrophilic, as described in the evaluation methods. The results are shown in the lower part of Figure 7.
[0072] As shown in the lower part of Figure 7, although a sheet-shaped artificial leather was obtained from sample 1, it cracked when bent and immediately fell apart when submerged in water. Sample 2 had low strength, and the tensile strength and tear load could not be measured. Sample 3 had a crunchy hard texture after drying and cracked when bent. Sample 4 fell apart and became slimy when submerged in water. Sample 5 was hard and tore when bent. Sample 6 also tore when bent. In contrast, samples 7 to 11 were flexible and did not crack when bent, and maintained their shape even when submerged in water. Furthermore, the tensile strength of samples 7 to 11 all greatly exceeded 0.2 MPa, and the tear load also exceeded 0.5 N / mm, indicating sufficient strength.
[0073] That is, the results of Sample 7 revealed that by blending "gelling agent, cellulose fiber, and animal and plant waste," artificial leather with bending resistance, tensile strength, tear strength, and shape retention when submerged in water can be produced. Also, the results of Sample 8 revealed that by blending "persimmon tannin, gelling agent, and animal and plant waste," artificial leather with bending resistance, tensile strength, tear strength, and shape retention when submerged in water can be produced. Also, the results of Samples 10 and 11 revealed that by blending "persimmon tannin, gelling agent, polyhydric alcohol, and cellulose fiber," artificial leather with bending resistance, tensile strength, tear strength, and shape retention when submerged in water can be produced.
[0074] <Example 9> Study of essential components 2 The artificial leathers of Samples 1 to 9 were prepared according to the formulation shown in the upper part of FIG. 8 and the preparation procedure described in Example 1(2). That is, Sample 1 was prepared by blending only persimmon skin (vegetable waste), Sample 2 was prepared by blending persimmon tannin and persimmon skin, Sample 3 was prepared by blending BC dispersion (cellulose fiber) and persimmon skin, Sample 4 was prepared by blending kappa carrageenan (gelling agent) and persimmon skin, Sample 5 was prepared by blending persimmon tannin, BC dispersion and persimmon skin, Sample 6 was prepared by blending persimmon tannin, kappa carrageenan, BC dispersion and persimmon skin, Sample 7 was prepared by blending persimmon tannin, kappa carrageenan and persimmon skin, Sample 8 was prepared by blending kappa carrageenan, BC dispersion and persimmon skin, and Sample 9 was prepared by blending persimmon tannin and kappa carrageenan. The thickness of the prepared artificial leathers was measured, their appearances were photographed, and their bending resistance, tensile strength, tear load and shape retention when hydrophilic were evaluated as described in the evaluation method. The results are shown in the lower part of FIG. 8.
[0075] As shown in the lower part of FIG. 8, sample 1 cracked when bent, had low strength, its tensile strength was not measurable, and its tear load was less than 0.5 N / mm. Sample 2 also cracked when bent, had low strength, and its tear load was not measurable. Sample 3 had a tear load less than 0.5 N / mm. Sample 4 crumbled when submerged in water. Sample 5 tore when bent. Sample 9 was also hard and tore when bent. In contrast, samples 6 to 8 did not crack when bent and maintained their shape even when submerged in water. Furthermore, the tensile strength of samples 6 to 8 all greatly exceeded 0.2 MPa, and the tear load also exceeded 0.5 N / mm, indicating that they had sufficient strength.
[0076] That is, the results of Sample 7 made it clear that by blending "persimmon tannin, gelling agent, and animal and vegetable waste," it was possible to produce artificial leather that had bending resistance, tensile strength, tear strength, and shape retention when submerged in water. Also, the results of Sample 8 made it clear that by blending "gelling agent, cellulose fiber, and animal and vegetable waste," it was possible to produce artificial leather that had bending resistance, tensile strength, tear strength, and shape retention when submerged in water.
[0077] <Example 10> Examination of the blending ratio of persimmon tannin The artificial leathers of Samples 1 to 7 were produced according to the composition shown in the upper part of FIG. 9 and the production procedure described in Example 1(2). That is, the content of persimmon tannin in the artificial leather was 0% by mass for Sample 1, 0.10% by mass for Sample 2, 0.98% by mass for Sample 3, 5.02% by mass for Sample 4, 9.75% by mass for Sample 5, 18.18% by mass for Sample 6, and 29.97% by mass for Sample 7. The thickness of the produced artificial leathers was measured, their appearances were photographed, and their bending resistance, tensile strength, tear load, and shape retention when hydrophilic were evaluated as described in the evaluation method. The results are shown in the lower part of FIG. 9.
[0078] As shown in the lower part of FIG. 9, sample 1 crumbled when submerged in water. On the other hand, samples 2 to 7 did not crack when folded. The tear loads of samples 2 to 7 were larger than that of sample 1, and all of them were significantly stronger than 0.5 N / mm, so they had sufficient strength. The tensile strengths of samples 2 to 7 were also significantly higher than 0.2 MPa, so they maintained their shape even when submerged in water. In other words, the artificial leather containing 0.1 to 29.97 mass% of persimmon tannin had higher shape retention and tear strength when submerged in water than the artificial leather containing no persimmon tannin. They also had sufficient bending resistance and tensile strength. These results demonstrate that persimmon tannin can impart water resistance and tear strength to artificial leather, and can be blended into artificial leather regardless of its content.
[0079] <Example 11> Examination of the blending ratio of gelling agent The artificial leathers of Samples 1 to 6 were produced according to the formulation shown in the upper part of Fig. 10 and the production procedure described in Example 1 (2). That is, the content of kappa-type carrageenan in the artificial leather was 0 mass% for Sample 1, 2.03 mass% for Sample 2, 4.05 mass% for Sample 3, 8.10 mass% for Sample 4, 27.27 mass% for Sample 5, and 40.50 mass% for Sample 6. The thickness of the produced artificial leathers was measured, their appearances were photographed, and their bending resistance, tensile strength, tear load, and shape retention when hydrophilic were evaluated as described in the evaluation method. The results are shown in the lower part of Fig. 10.
[0080] As shown in the lower part of FIG. 10, sample 1 was hard and broke when bent. Also, because it was hard and brittle, it broke when cut out, making it impossible to prepare a test piece, and it was impossible to measure the tensile strength and tear load. Sample 2 cracked when bent. On the other hand, samples 3 to 6 did not crack when bent and were flexible. They maintained their shape even when submerged in water. Furthermore, the tensile strength of samples 3 to 6 was far greater than 0.2 MPa, and the tear load was far greater than 0.5 N / mm, so they had sufficient strength. Furthermore, samples 3 to 6 maintained their shape even when submerged in water. That is, the artificial leather containing 4.05 to 40.50 mass% of kappa carrageenan had higher bending resistance (flexibility) than those containing no kappa carrageenan or 2.03 mass% of kappa carrageenan. In addition, the tensile strength, tear strength, and shape retention when submerged in water were also sufficient. These results demonstrate that the gelling agent can impart bending resistance and flexibility to the artificial leather, and that it is preferable for the gelling agent to be contained in the artificial leather at a content of more than 2% by mass.
[0081] <Example 12> Examination of the blending ratio of polyhydric alcohol Artificial leathers of samples 1 to 5 were produced according to the formulation shown in the upper part of Fig. 11 and the production procedure described in Example 1 (2). That is, the content of sorbitol in the artificial leather was 0 mass% for sample 1, 41.39 mass% for sample 2, 50.14 mass% for sample 3, 59.36 mass% for sample 4, and 85.12 mass% for sample 5. For the produced artificial leathers, the thickness was measured, the appearance was photographed, and the bending resistance, tensile strength, tear load, and shape retention when hydrophilic were evaluated as described in the evaluation method. The results are shown in the lower part of Fig. 11.
[0082] As shown in the lower part of FIG. 11, although none of Samples 1 to 5 cracked when bent, Samples 2 to 5 had higher flexibility and a softer texture than Sample 1. In addition, the tensile strength of Samples 2 to 5 was significantly greater than 0.2 MPa, and the tear load was also greater than 0.5 N / mm, so that they had sufficient strength. In addition, all of Samples 2 to 5 maintained their shape even when submerged in water. In other words, the artificial leather containing 41.39 to 85.12 mass% of sorbitol was more flexible and had a better texture than the artificial leather not containing sorbitol. In addition, the tensile strength, tear strength, and shape retention when submerged in water were also sufficient. From these results, it was revealed that polyhydric alcohol can impart high flexibility and soft texture to artificial leather, and can be blended into artificial leather regardless of its content ratio.
[0083] Example 13: Study on the blending ratio of cellulose fibers Artificial leathers of samples 1 to 6 were produced according to the composition shown in the upper part of Fig. 12 and the production procedure described in Example 1 (2). That is, the content of cellulose fiber in the artificial leather was 0 mass% for sample 1, 5.01 mass% for sample 2, 5.40 mass% for sample 3, 5.98 mass% for sample 4, 10.03 mass% for sample 5, and 19.52 mass% for sample 6. The thickness of the produced artificial leathers was measured, their appearances were photographed, and their bending resistance, tensile strength, tear load, and shape retention when hydrophilic were evaluated as described in the evaluation method. The results are shown in the lower part of Fig. 12.
[0084] As shown in the lower part of FIG. 12, the tensile strength values were greatest in the following order: Sample 6>Sample 5>Sample 4>Sample 3>Sample 2>Sample 1. Moreover, the tear loads of Samples 2 to 6 all exceeded 0.5 N / mm, and thus had sufficient strength. Moreover, all of Samples 2 to 6 did not crack when bent, and retained their shape even when submerged in water. In other words, the greater the cellulose fiber content, the higher the tensile strength. Moreover, all of the artificial leathers containing 5.01 to 19.52 mass% of cellulose fiber had sufficient bending resistance, tear strength, and shape retention when submerged in water. These results demonstrate that cellulose fiber can impart high tensile strength to artificial leather, and can be incorporated into artificial leather regardless of the content ratio of cellulose fiber.
[0085] <Example 14> Study of gelling agent 2 Artificial leather samples 1 to 5 were prepared according to the formulation shown in the upper part of Fig. 13 and the preparation procedure described in Example 1(2). That is, as a gelling agent, kappa-type carrageenan was blended in sample 1, locust bean gum and xanthan gum in sample 2, locust bean gum and tamarind gum in sample 3, starch in sample 4, and gelatin in sample 5. As described in the evaluation method, the thickness of the prepared artificial leather was measured, its appearance was photographed, and it was evaluated for bending resistance, tensile strength, tear load, and shape retention when hydrophilic. The results are shown in the lower part of Fig. 13.
[0086] As shown in the lower part of FIG. 13, all of Samples 1 to 5 did not crack when bent and maintained their shape even when submerged in water. In addition, the tensile strength was well above 0.2 MPa and the tear load was well above 0.5 N / mm, providing sufficient strength. In other words, when kappa carrageenan, locust bean gum, xanthan gum, tamarind gum, starch and / or gelatin were used as the gelling agent, artificial leathers with bending resistance, tensile strength, tear strength and shape retention when submerged in water could be produced. These results made it clear that any type of gelling agent, such as proteins or various polysaccharides, can be used.
[0087] <Example 15> Study on animal and plant waste 2 Artificial leather samples 1 to 4 were produced according to the formulation shown in the upper part of Fig. 14 and the production procedure described in Example 1(2). That is, as vegetable waste, sample 1 contained apple skin, sample 2 contained white peach skin, sample 3 contained carrot pomace, and sample 4 contained persimmon skin. As described in the evaluation method, the thickness of the produced artificial leather was measured, its appearance was photographed, and it was evaluated for bending resistance, tensile strength, tear load, and shape retention when hydrophilic. The results are shown in the lower part of Fig. 14.
[0088] As shown in the lower part of FIG. 14, all of Samples 1 to 4 did not crack when bent and maintained their shape even when submerged in water. In addition, all of Samples 1 to 4 had sufficient strength, with tensile strengths far exceeding 0.2 MPa and tear loads far exceeding 0.5 N / mm. In other words, whether apple peel, white peach peel, astringent persimmon peel, or carrot pomace was used as the animal and plant waste, artificial leather with bending resistance, tensile strength, tear strength, and shape retention when submerged in water could be produced. This result made it clear that any type of animal and plant waste could be used.
[0089] Example 16: Examination of the mixing ratio of animal and plant waste The artificial leathers of Samples 1 to 8 were produced according to the composition shown in the upper part of FIG. 15 and the production procedure described in Example 1(2). That is, the content of vegetable waste (carrot pomace or persimmon peel) in the artificial leather was 0 mass% for Sample 1, 30.78 mass% for Sample 2, 53.82 mass% for Sample 3, 58.53 mass% for Sample 4, 69.40 mass% for Sample 5, 70.65 mass% for Sample 6, 76.92 mass% for Sample 7, and 95.02 mass% for Sample 8. The thickness of the produced artificial leathers was measured, their appearances were photographed, and their bending resistance, tensile strength, tear load, and shape retention when hydrophilic were evaluated as described in the evaluation method. The results are shown in the lower part of FIG. 15.
[0090] As shown in the lower part of FIG. 15, none of Samples 1 to 8 cracked when bent. The tensile strength of Samples 1 to 8 was far greater than 0.2 MPa. The tear load of Samples 2 to 8 was also greater than 0.5 N / mm, which was greater than that of Sample 1. All of Samples 1 to 8 maintained their shape even when submerged in water. In other words, artificial leather containing 30.78 to 95.02 mass% of vegetable waste had a higher tear load and was stronger than that of an artificial leather not containing vegetable waste. In addition, the artificial leather had sufficient bending resistance, tensile strength, and shape retention when submerged in water. These results revealed that animal and vegetable waste can impart high tear strength to artificial leather, and can be blended into artificial leather regardless of the content ratio.
Claims
1. The artificial leather comprises persimmon tannin, a gelling agent, a polyhydric alcohol and cellulose fibers.
2. The artificial leather comprises persimmon tannin, a gelling agent and animal and plant waste.
3. An artificial leather comprising a gelling agent, cellulose fibers and animal and plant waste.
4. The artificial leather according to claim 1, comprising the persimmon tannin, the gelling agent, the polyhydric alcohol and the cellulose fiber in the following solid contents: Persimmon tannin: 0.1% by mass or more and 30% by mass or less, Gelling agent: more than 2% by mass to 45% by mass, Polyhydric alcohol: more than 0% by mass to 90% by mass or less, Cellulose fiber: more than 0% by mass and 30% by mass or less.
5. The artificial leather according to claim 2, containing the persimmon tannin and the gelling agent in the following solid content ratios: Persimmon tannin: 0.1% by mass or more and 30% by mass or less, Gelling agent: more than 2% by mass to 45% by mass, Animal and plant waste: more than 0% by mass to 97% by mass or less.
6. The artificial leather according to claim 3, comprising the gelling agent and the cellulose fiber in the following solid content ratios: Gelling agent: more than 2% by mass to 45% by mass, Cellulose fiber: more than 0% by mass and 30% by mass or less. Animal and plant waste: more than 0% by mass to 97% by mass or less.
7. A dissolving step of heating a mixture selected from the group consisting of the following (A) to (C) to a temperature at which the gelling agent dissolves to obtain a dissolved product; (A) A mixture containing persimmon tannin, a gelling agent, a polyhydric alcohol, cellulose fiber and water. (B) A mixture containing persimmon tannin, a gelling agent, animal and plant waste, and water. (C) a mixture comprising a gelling agent, cellulose fibers, animal and plant waste, and water; a molding step of forming the melt into a predetermined shape and then solidifying the melt by dissipating heat to obtain a solidified product; a drying step of drying the solidified material; A method for producing artificial leather comprising the steps of:
Citation Information
Patent Citations
Sheet-like object
JP2019044292A